2018
DOI: 10.3390/molecules23030626
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Thioxanthones as Modulators of P-glycoprotein: Synthesis and Enantioselectivity Studies

Abstract: Recently, thioxanthone derivatives were found to protect cells against toxic P-glycoprotein (P-gp) substrates, acting as potent inducers/activators of this efflux pump. The study of new P-gp chiral modulators produced from thioxanthone derivatives could clarify the enantioselectivity of this ABC transporter towards this new class of modulators. The aim of this study was to evaluate the P-gp modulatory ability of four enantiomeric pairs of new synthesized chiral aminated thioxanthones (ATxs) 1–8, studying the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 72 publications
1
19
0
Order By: Relevance
“…The results obtained concerning the evaluation of the OXs’ effects on P-gp expression and activity further reinforce that this approach of evaluation of both parameters has an important impact on the evaluation of the modulatory potential of new compounds. Furthermore, the data is in accordance with other reports that also suggest that alterations in P-gp expression do not linearly translate into similar changes in P-gp transport activity (which could be due to an insufficient time to guarantee complete protein function or incomplete membrane targeting) and increases in P-gp activity may occur without changes in protein expression [21,26,27,39]. In fact, Silva et al observed in Caco-2 cells that the strong increases in P-gp expression levels after exposure to doxorubicin (Dox) (reaching 646% after 24 h of incubation with 100 μM Dox when compared to control cells (100%)) were not translated into proportional increases in P-gp transport activity (150% after a 24 h incubation period with 100 μM Dox, when compared to control cells (100%)) [21].…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained concerning the evaluation of the OXs’ effects on P-gp expression and activity further reinforce that this approach of evaluation of both parameters has an important impact on the evaluation of the modulatory potential of new compounds. Furthermore, the data is in accordance with other reports that also suggest that alterations in P-gp expression do not linearly translate into similar changes in P-gp transport activity (which could be due to an insufficient time to guarantee complete protein function or incomplete membrane targeting) and increases in P-gp activity may occur without changes in protein expression [21,26,27,39]. In fact, Silva et al observed in Caco-2 cells that the strong increases in P-gp expression levels after exposure to doxorubicin (Dox) (reaching 646% after 24 h of incubation with 100 μM Dox when compared to control cells (100%)) were not translated into proportional increases in P-gp transport activity (150% after a 24 h incubation period with 100 μM Dox, when compared to control cells (100%)) [21].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, these thioxanthones were shown to behave as P-gp activators, increasing the efflux of substrates without interfering with P-gp levels of expression. Moreover, ( R )-1-((1-hydroxypropan-2-yl)amino)-4-propoxy-9 H -thioxanthen-9-one ( 89 ), after 24 h of incubation, was also able to significantly increased P-gp expression (P-gp inducer) [ 181 ]. Concerning thioxanthones induction mechanism, one of the possibilities is the transcriptional activation of the MDR1 gene expression that involves the activation of the pregnane X receptor (PXR) [ 182 , 183 ].…”
Section: A Library Of Natural Mimetic Xanthones Looking For Biologmentioning
confidence: 99%
“…Concerning thioxanthones induction mechanism, one of the possibilities is the transcriptional activation of the MDR1 gene expression that involves the activation of the pregnane X receptor (PXR) [ 182 , 183 ]. Furthermore, no significant differences were detected in the activity of the enantiomeric pairs towards P-gp [ 181 ]. Still concerning P-gp induction in other organisms, using high throughput RNA sequencing, the transcriptional response of the filamentous fungus Neurospora crassa to thioxanthone derivatives with antitumor activity ( 75 , 81 , and 86 ) revealed that there is an induction of ABC transporters in that fungus, particularly atrb and cdr4, which is a common consequence of the treatment with (thio)xanthones [ 94 ].…”
Section: A Library Of Natural Mimetic Xanthones Looking For Biologmentioning
confidence: 99%
“…Therefore, it was demonstrated that both enantiomers possess P-gp inhibition ability, with R enantiomer being more potent. It was demonstrated previously that P-gp can interact in a different way with enantiomers [48,49,50]. When chiral drugs modulate P-gp, one enantiomer can increase the activity of the pump, while the other enantiomer can inhibit its activity [51,52].…”
Section: Resultsmentioning
confidence: 99%